Interference mitigation for satellite-terrestrial heterogeneous coexistence cognitive MIMO system based on DBF - Yong LIAO; Tao WANG; Huan CHEN; Xin ZHOU; Yu-feng LI (Tongxin xuebao)
For the coexistence and increasing interference of satellite-terrestrial network and terrestrial wireless network,a typical scenario where the geostationary earth orbit (GEO) satellite-terrestrial network and the 4G mobile communication network coexist heterogeneously was analyzed.Besides,a multi-user cognitive system model that secondary satellite terminals interfere the primary multiple input multiple output (MIMO) 4G based stations was also proposed,with whose general signal processing was deduced.Meanwhile,digital beam forming (DBF) technology in 4G based station system was adopted to minimize the cognitive interference caused by multi-antennas and multi-users.And an optimal beam weight based on fixed azimuth interference (OBW-FAI) was proposed.Weight vector was only related to the azimuth of the interferences,thus the proposed algorithm does not need real-time and repeat calculations,and had small complexity.Finally,the numerical simulation results verify that the proposed system and algorithm can effectively reduce interference between satellite-terrestrial network and terrestrial wireless network to a certain extent.